An Irish Race Convention? Body Politics and the 1924 Tailteann Games. (December 2019) - Heffernan, Conor
Covering the 1924 Tailteann Games, a 2-week sporting and cultural celebration held in the Irish Free State, the following article explores the broader sociocultural significance of the Tailteann's opening ceremony. Said to be the restoration of an ancient Irish festival, the Tailteann Games were envisioned as an Irish 'race Olympiad' open to those born in Ireland and those of Irish descent. Welcoming visitors from several nations, the festival marked an ambitious effort on the part of its organisers to formally announce the newly independent state onto the world stage. While previous studies on the Tailteann Games of 1924 have depicted it as an attempt to project a certain kind of Irish identity, the present article seeks to specify the meaning of this identity in much greater detail. Surveying the use of ancient folklore, mass gymnastic displays and modern technologies during the opening ceremony, it is argued that the 1924 Games sought to depict the Irish Free State as a young, modern and culturally vibrant state. The article thus highlights efforts to project a specific and definitive form of Irish identity during the Free State's opening years.